Impact of Integrating Rumke Statistics to Assist with Choosing Between Automated Hematology Analyzer Differentials vs Manual Differentials. (15th October 2019) - Stephens, Laura; Hintz-Prunty, Wendy; Bengtsson, Hans-Inge; Proudfoot, James A; Patel, Sandip Pravin; Broome, H Elizabeth
Abstract: Background: To optimize precision of nucleated blood cell counting, the clinical laboratory scientist should post the automated differential rather than the manual differential if the former is within the 95% CI of the latter, as determined by the "Rumke statistic." The objective of this study was to determine the potential impact of real-time, computer-assisted use of Rumke statistics for more judicious use of the automated vs digitally imaged, manual differential. Methods: Complete blood counts with automated differentials produced by a XE5000™ hematology analyzer (Sysmex) were compared with both the DM96 (CellaVision™ AB) preclassification differentials and the posted reclassified manual differentials, using the Rumke 95% CIs as calculated using the Clopper-Pearson method. Results: A total of 44.7% of manual differentials had no statistical or clinical justification over the automated differential. In addition, 31.1% of manual differentials had statistical discrepancies between the instrument absolute neutrophil count (IANC) and manual absolute neutrophil count (ANC). Nineteen of these IANC/manual ANC discrepant samples had ANCs below 1500/μL, a decision level for cancer treatment. Holding the IANC when it is less than 2000/μL until after manual smear review would have prevented the posting of any IANC vs manual ANC discrepant results at the 1500/μL ANC decision threshold. Conclusions: A real-time operator alert concerning the statistical identity of imaging device differentials vs automated differentials could have reduced manual differentials by nearly 45%. Not posting unnecessary manual differentials for the cases with IANC/manual ANC discrepancies would have likely reduced clinical error/confusion.